Sentiment Analysis : A Review - Sharma, Hemlata; Maloo, Aishwarya; Sharma, Kirti; Rani, Simran (International Journal of Psychosocial Rehabilitation, 2020)
Authors' views on certain items are discovered using the process of sentiment analysis (also known as opinion mining). It is the views created by thought leaders and ordinary people that have an impact on the decision-making process of individuals. The majority of the time, when someone wants to buy something online, they will start by looking for reviews and comments posted by other people about the various options. One of the trendiest study fields in computer science nowadays is sentiment analysis (also known as emotional computing). The subject has been the subject of more than 7,000 articles. Sentiment analysis solutions are being developed by hundreds of startups, and major statistical programs such as sas and spss contain sentiment analysis modules as standard features. Today, there is a massive expansion of sentiments accessible through social media platforms such as twitter, Facebook, message boards, blogs, and user forums, among others. The information included in these bits of text is a gold mine for businesses and people who wish to monitor their reputation and receive quick feedback on their products and conduct.